2009
DOI: 10.1016/j.jhealeco.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of the healthcare costs of obesity

Abstract: Who pays the healthcare costs associated with obesity? Among workers, this is largely a question of the incidence of the costs of employer-sponsored coverage. Using data from the National Longitudinal Survey of Youth and the Medical Expenditure Panel Survey, we find that the incremental healthcare costs associated with obesity are passed on to obese workers with employer-sponsored health insurance in the form of lower cash wages. Obese workers without employer-sponsored insurance do not have a wage offset rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 19 publications
3
92
3
2
Order By: Relevance
“…For men, I find no effects on employment prospects. Sex-specific heterogeneity in the labor-market effects of obesity has been found previously (e.g., Morris, 2006Morris, , 2007Bhattacharya and Bundorf, 2009). The analysis further shows that weight loss is significantly associated with improvements in proxy variables for labor productivity in obese women.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…For men, I find no effects on employment prospects. Sex-specific heterogeneity in the labor-market effects of obesity has been found previously (e.g., Morris, 2006Morris, , 2007Bhattacharya and Bundorf, 2009). The analysis further shows that weight loss is significantly associated with improvements in proxy variables for labor productivity in obese women.…”
Section: Introductionsupporting
confidence: 62%
“…6 The link between obesity and employment prospects has been extensively analyzed in the literature. While the majority of the studies focuses on the effect of obesity on wages (e.g., Register 2 A model on the potential mediators of obesity on labor market outcomes is presented by Baum and Ford (2004) as well as by Bhattacharya and Bundorf (2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is more than a subtle difference for several reasons. First, we can rule out health and health benefits (Bhattacharya and Bundorf, 2009) as the main reasons for an impact of bodyweight on wages, given that women's wages peak at BMI levels that cannot possibly reflect health constraints. Second, our findings indicate that women with BMIs that are most consistent with societal standards of physical attractiveness earn the highest wages.…”
Section: Conlcusion and Discussionmentioning
confidence: 99%
“…Pauly and Herring (1999) found that predicted medical expenditures have a negative impact on the wages of older workers. Bhattacharya and Bundorf (2009) found a significant wage differential between obese and thinner women for those covered by health insurance, but no differential for those without insurance. While all of these studies are consistent with the predictions from the theory, on the whole, there is very little direct evidence that increases in health insurance premiums are fully offset by a decline in cash compensation .…”
Section: The Relationships Between Health Insurance Premiums Wages Amentioning
confidence: 82%